Komodifikasi Agama Dan Simbol Keagamaan ‘Jilbab’ Di Media Online Dalam Persepsi Netizen - Farhan Farhan; Faisul Islamiyah (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
The purpose of this study is to provide information to the public about Islamic law in covering the aurat and revealing the commodification and obscurity of the meaning of religious symbols. This study uses a critical paradigm with the study of political communication. Commodification plays its role in giving influence and signs for Muslim fashion usage. Where religious symbols (headscarves) basically have a very meaningful religious value, even highly recommended in their use. In collecting data, this research uses virtual ethnographic analysis with objects of visual studies in good cyber media in the form of photo publications and social media views. The results showed that religious symbols (headscarves) had been commodified, obscured and even exploited as commodities to be traded. The development of using social media, causing religious symbols (headscarves) can be enjoyed so widely by the community. Where internet citizens or netizens can play a role as a controller or actor of information that is being discussed, that is controlling the thinking of a message, which will give birth to perceptions of the internet community or other netizens.